IBD sharing patterns as intra-breed admixture indicators in small ruminants - Da Silva, Stéphane; Mwacharo, Joram; Li, Meng-Hua; Ahbara, Abulgasim; Catherine Muchadeyi, Farai; Dzomba, Edgar; Lenstra, Johannes; Silva, Anne da (Springer Nature [academic journals on nature.com], 2025)
In this study, we investigated how IBD patterns shared between individuals of the same breed could be informative of its admixture level, with the underlying assumption that the most admixed breeds, i.e. the least genetically isolated, should have a much more fragmented genome. We considered 111 goat breeds (i.e. 2501 individuals) and 156 sheep breeds (i.e. 3304 individuals) from Europe, Africa and Asia, for which beadchip SNP genotypes had been performed. We inferred the breed’s level of admixture from: (i) the proportion of the genome shared by breed’s members (i.e. “genetic integrity level” assessed from ADMIXTURE software analyses), and (ii) the “AV index” (calculated from Reynolds’ genetic distances), used as a proxy for the “genetic distinctiveness”. In both goat and sheep datasets, the statistical analyses (comparison of means, Spearman correlations, LM and GAM models) revealed that the most genetically isolated breeds, also showed IBD profiles made up of more shared IBD segments, which were also longer. These results pave the way for further research that could lead to the development of admixture indicators, based on the characterization of intra-breed shared IBD segments, particularly effective as they would be independent of the knowledge of the whole genetic landscape in which the breeds evolve. Finally, by highlighting the fragmentation experienced by the genomes subjected to crossbreeding carried out over the last few generations, the study reminds us of the need to preserve local breeds and the integrity of their adaptive architectures that have been shaped over the centuries.